ANALISIS PERBANDINGAN PENERIMAAN ELEKTRONIK SPT MASA PPN SERTA REALISASI PENERIMAAN PPN SEBELUM DAN SESUDAH PENERAPAN KEBIJAKAN PER-11/PJ/2013 (Studi Pada Kpp Pratama Singosari Malang Tahun 2012-2014) - Haryono, . (Jurnal Mahasiswa Perpajakan, 2015)
This study aims to analyze comparison of electronic periodic VAT return (e-VAT) acceptance, taxpayer compliance ratio in reporting periodic e-VAT return and VAT revenues were realized before and after the implementation of PER-11/PJ/2013 on Primary Tax Office in Singosari Malang. This study also explained generally the implementation, the supporting factors and obstacles of this policy. The results noted that this policy increased the effectiveness and efficiency in administrative system because of paperless. The supporting factors in this application was any socialization, SMS Service and consulting services with the Account Representative. The appeared obstacle such as the difficulty to understanding the content of socialization program, trouble in e-VAT program and the limited number of personnel. In average periodic e-VAT return acceptance and taxpayer compliance ratio to reporting periodic e-VAT return was any difference because there was an increase compared to the previous policy, meanwhile the average of VAT receipts did not have differences. Researcher gave advices to continue the activity than could increase taxpayer compliance and as well as did collaborate with government and private agencies to determine the financial transactions of registered taxpayers. Keywords: e-VAT, Compliance, Tax Policy Abstrak Penelitian ini bertujuan untuk menganalisa perbandingan penerimaan e-SPT Masa PPN, Rasio kepatuhan PKP dalam melaporkan e-SPT Masa PPN dan Realisasi penerimaan PPN sebelum dan sesudah penerapan PER-11/PJ/2013 di KPP Pratama Singosari. Penelitian ini juga menjelaskan secara umum penerapan, faktor pendukung dan penghambat dalam kebijakan ini. Hasilnya diketahui bahwa kebijakan ini meningkatkan efektivitas dan efisiensi pada sistem administratif karena paperless. Faktor pendukung dalam penerapannya adalah adanya sosialisasi, Layanan SMS dan layanan konsultasi dengan Account Representative. Hambatan yang nampak adalah sulitnya untuk memahami isi dalam program sosialisasi, permasalahan pada program e-SPT dan terbatasnya jumlah personil. Rata-rata penerimaan e-SPT Masa PPN dan rasio kepatuhan PKP dalam melaporkan e-SPT Masa PPN memiliki perbedaan karena terdapat peningkatan dibandingkan kebijakan sebelumnya, sedangkan rata-rata penerimaan PPN tidak memiliki perbedaan. Peneliti menyarankan untuk melanjutkan upaya yang dapat meningkatkan kepatuhan Wajib Pajak dan menjalin kerjasama dengan badan pemerintahan maupun swasta untuk mengetahui segala transaksi Wajib Pajak. Kata kunci :Â  e-SPT, Kepatuhan, Kebijakan Pajak